3 - Remaking from Below: The Political and Policy Implications of Subaltern Experiences in Postcolonial Freetown - Ibrahim Abdullah (Afrika Zamani, 2022)
This article deals with the archaeology of violence and urban exclusion in postcolonial Freetown. It argues that subalterns underwent a double exclusion – from the colonial to the postcolonial: first as natives on the basis of race, and then subsequently, as a marginal economic category. Their dogged resistance to structuration from above compels us to rethink the city and the citizenry in new ways that challenge our conception of urbanization, citizenship and the nation state in contemporary Africa. The article is divided into three sections. The first section discusses colonial restrictions from above and the exclusion of natives in the colonial city based on race. The second section examines the postcolonial divide and the reinvention of the natives as subalterns within the prism of class. The third section deals with the monumental changes that continue to make and remake post-war Freetown and the travails of the urban poor.